Utilization of the Inshot Application as a Learning Media - Melisa Rezi; Adam Mudinilllah (Al-Madrasah: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
This study aims to explain the use and how to edit the inshot video editing application as a learning medium in elementary schools during the COVID-19 pandemic. This study uses a qualitative descriptive research method by describing the inshot application to receive an explanation of the use and use of the inshot application in making a video-based learning media. In the current era, digital technology has developed very rapidly in the world, including Indonesia. And this includes education as a result, due to the COVID-19 pandemic. So, the solution given by the government at this time is to carry out the learning process online or remotely, which is generally called online school. And technology at this time has become one of the indispensable tools in using learning media such as the use of inshot applications. because the media has a video editing feature that can help an educator in communicating with students face-to-face through online media. Almost all schools in Indonesia also use learning media that use the inshot application.